Pentingnya Kesadaran Berbahasa: Upaya Meningkatkan Penggunaan Bahasa Indonesia yang Benar di Era Digital - Adelia Br Aritonang; Dana Diva Ivan De La Pena Ginting; Nazwa Clarissa; Rendi Jonatan Lumbangaol; Shinta Uli Nainggolan; Nurul Azizah (Politeknik Kampar, 2025)
The development of Indonesian in the digital era is a complex phenomenon influenced by information and communication technology (ICT), globalization, and the behavior of modern society. This transformation presents challenges in maintaining the authenticity and quality of Indonesian, especially with the widespread use of slang, abbreviations, and foreign terms on social media. This study aims to increase language awareness among the community, especially the younger generation, through effective education and training. The method used is a literature study, which collects and analyzes various sources of related literature. The results of the study show that high language awareness can encourage the use of good and correct Indonesian, and avoid the negative influence of foreign languages. Efforts to increase language awareness must involve various parties, including the government, educational institutions, and the community, to ensure that Indonesian remains sustainable and relevant amidst the development of the times. Thus, the importance of integrating digital literacy education and language policies that support the use of standard language is key to maintaining the existence of Indonesian in this digital era.